Reading Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Precipitating stimuli, including eye-movements, reading aloud versus reading silently, linguistic complexity, and concentration, were investigated in a 24 year old young woman with reading epilepsy seen in the Division of Neurology and Clinical Neurophysiology Laboratory, University of Ottawa General Hospital, and Depts of Psychology and Computer Engineering, Carleton University, Ottawa, Ontario, Canada.